Electronic Document Circulation As a Factor of Efficient Managing the Organizations’ Business Processes - O. N. Chemodanova; G. Yu. Grib (Управленческие науки, 2017)
The factors of forming and implementing the system of managing the organizations’ business processes in the form of electronic document circulation corporate system (EDCCS) enabling to avoid the excessive paper document circulation are considered in the article. On the basis of statistic data the organization activity before and after implementing the EDCCS has been analyzed. The factors of direct and indirect effect gained from the usage of this system are distinguished. In the result of analysis the conclusion is made about practicability of implementing and using the EDCCS in the organization activity boosting efficiency growth and rationality of the organizations units’ interaction in order to achieve the goals set by them.